The Effect of Consumer Behavior and Financial Literacy on Financial Satisfaction of the Millennial Generation with Financial Stress Mediation - Farida Fatmawati; Rifa'atul Maftuhah; Rahila Amanatul Ummah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study analyzes the influence of consumer behavior and financial literacy on financial satisfaction with financial stress as a mediating variable in the millennial generation in Surabaya. The research used a quantitative approach with an explanatory survey through an online questionnaire aimed at millennials aged 29-40 years who are active users of digital financial services. Data analysis was performed using Partial Least Squares- Structural Equation Modeling (PLS-SEM). The results of the study show that consumer behavior has a negative effect on financial satisfaction, while financial literacy has a positive and significant effect. Financial stress acts as a mediator, indicating that impulsive consumption tendencies and low financial capacity can increase psychological stress and decrease an individual's financial well-being. These findings underscore the importance of improving financial literacy and controlling consumer behavior to strengthen millennials' financial satisfaction in the digital era. This research provides practical implications for policy makers and financial institutions in designing more targeted financial education programs.